Influence of Emotional Intelligence on Academic Achievement among Students at Secondary Schools in Babylon City - Hadeel Sahib Ali1, Qahtan Qassim Mohammed1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: The main aim of the study is to determine the influence of emotional intelligence on academic achievement among the students. A descriptive study is carried to assess the influence of emotional intelligence on academic achievement among Students at secondary schools in Babylon City. A systematic random sample of (586) students are selected throughout the use of probability approach. The study sample selected from (4) secondary schools, which divided into (2) schools for female and (2) schools for male. The selection of sample divided into (141) students for each of male school and (152) for each female school. The schools were randomly chosen by lottery in the purpose to select 4 schools out of 28 schools (15%) and 25% of the students in these schools, which was convenient to the investigator. A total of (650) secondary school students, they were met the study criteria and agreed to contribute in the study The finding reveals that there is a significant influence of students’ emotional intelligence on academic achievement at p-value= 0.01